2011
DOI: 10.3109/08880018.2011.563772
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Echocardiography Versus Cardiac Troponin I levels in the Early Detection of Anthracycline Cardiotoxicity in Childhood Acute Leukemia: Prospective Evaluation of a 7-Year-Long Clinical Follow-up

Abstract: The present study was designed to evaluate the significance of echocardiography versus cardiac troponin I levels in early detection of anthracycline dependent cardiotoxicity in acute lymphoblastic leukemia (ALL) patients. A total of 276 pediatric ALL patients were included in the study prospectively along 3 phases of data collection lasted from 2002 to 2009; including phase I (March 2002 to February 2003; n = 25; 53.3% females), phase II (September 2003 to April 2004; n = 35; 57.1% females), and phase III (Jan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…*Abnormal value. cTnI was not useful in the detection of an early stage anthracycline-associated cardiotoxicity (20). El-Shitany et al (21) showed an elevation during treatment to be associated with an impaired systolic function and pretreatment with carvedilol seemingly protective.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…*Abnormal value. cTnI was not useful in the detection of an early stage anthracycline-associated cardiotoxicity (20). El-Shitany et al (21) showed an elevation during treatment to be associated with an impaired systolic function and pretreatment with carvedilol seemingly protective.…”
Section: Discussionmentioning
confidence: 98%
“…Few studies have reported on paediatric patients during malignancy treatment (20,21) and only one during later follow-up (13). One reported that Tables 2 and 3.…”
Section: Discussionmentioning
confidence: 99%
“…TnI is more feasible than the other cardiac troponins for early CIC diagnosis due to its kinetic curve [18], but the exact dynamic of troponin release into bloodstream is not well known [5,12,19]. Although several papers have been published regarding CIC evaluation by troponin measurements, there are only a few studies on this subject in pediatric ALL setting [20][21][22][23][24][25][26][27][28][29]. Different groups monitored large cohorts of children with ALL and concluded that TnI was predictable for myocardial injury [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…Monitoring purely based on symptoms might miss the chance to detect cardiotoxicity early and may eventually lead to an irreversible cardiac failure. Cardiac biomarkers and dynamic imaging studies such as 2D echocardiography can help in the early detection of AIC 10. Dobutamine stress Echo, nuclear ventriculography and cardiac MRI are other effective tools to assess for cardiac damage in the setting of ongoing chemotherapy but relatively time-consuming 11…”
Section: Discussionmentioning
confidence: 99%